Performance of Sal (Shorea robusta) on Soils Derived from Different Parent Materials in Shahdol forest Division, M.P. - Totey, N. G.; Bhowmik, A. K.; Khatri, P. K. (Indian Forester, 1986)
Performance of Salon soils derived from sand stone, granite, trap with lateritic bricks, deccan trap and mottled nodular bed of limestone was studied in Shahdol Forest Division, M.P. According to phytosociological considerations Shorea robusta- Madhuca indica, Shorea robusta-Terminalia tomentosa, Terminalia tomentosa- Lagerstroemia parviflora and Terminalia communities were found on sand stone, trap with lateritic bricks, deccan trap and limestone respectively. Sal (Shorea robusta) had maximum frequency, density, basal area and also IVI on soils derived from sand stone and minimum on soils derived from limestone. This differential response of salon sand stone (and also granite) was explained on the basis of physico-chemical properties of the soils. Sal prefers soil low in pH (5.4 to 6.5), low in electrical conductivity (âˆ 0.1 mmhos/cm), low in Exch. Ca (3 to 10 meq/lOO gm), low in Mg (1 to 4 meq/100 gm) and also low in C.E.C. (6 to 20 meq/l00 gm).